Palpomyia ryszardi sp. n. from Peru (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2013)
A new species of the Palpomyia tibialis group, Palpomyia ryszardi, is described from male and female specimens and from their pupal exuviae from material collected in the vicinities of Iquitos in Peruvian Amazonia. The adult is compared with the most similar Neotropical congener, Palpomyia pseudolacustris SPINELLI & DIPPOLITO, and the pupa with the American species Palpomyia subaspera (COQUILLETT). Descriptions are accompanied by photographs and ink illustrations.